Analisis Kesesuaian Lahan Tanaman Padi di Nagari Panampuang Kecamatan Ampek Angkek Kabupaten Agam Berbasis Sistem Informasi Geografi (SG) - Ernawati, Ernawati; Zulva, MartaPoli (Lembaga Yasin AlSys, 2025)
This study aims to analyze land suitability for rice cultivation in Nagari Panampuang using Geographic Information Systems (GIS) and the matching method. This method compares land characteristics, such as soil texture, slope, water availability, and climate, with the growth requirements of rice plants. The data used include topographic maps, land use maps, and climate and soil data. The analysis results show that most areas in Nagari Panampuang have varying levels of land suitability for rice cultivation, with some locations recommended for further development. Map overlays indicate that S1 land (Highly Suitable) covers 226 hectares in Jorong Kubu, Surau Labuah, Surau Lauik, and Lurah, with highly supportive conditions. S2 land (Moderately Suitable), covering 17 hectares in Surau Labuah, has minor constraints, while S3 land (Marginally Suitable), covering 116 hectares in Bonjo, Lundang, and Sungai Baringin, has significant limitations. S1 land has the greatest potential, while S2 and S3 lands require more effective management.